Validation of Modified COPCORD Questionnaire Indonesian Version as Screening Tool for Joint Pain and Musculoskeletal Diseases - Anshory, Muhammad; Wahono, Cesarius Singgih; Kalim, Handono; Al Rasyid, Harun (Indonesian Rheumatology Association, 2018)
Background: WHO-ILAR COPCORD Program is a program that aimed to obtain data on joints pain and musculoskeletal diseases in developing countries, one aspect which has not been studied is the ability of COPCORD questionnaire as a screening tool which standardized for screening joint pain and musculoskeletal diseases. Objective of this study is to assess the validity of modified COPCORD questionnaire Indonesian version in screening joint pain and musculoskeletal disease compared to examination by rheumatologists.Methods: The initial phase of the research is determining essential points, translation to Indonesian, and back translation. The second stage is testing questionnaires in communities which 100 respondents involved. Dependent variable is the diagnosis of rheumatic diseases and independent variables are pain in less and more than 7 days, high degree pain in less and more than 7 days, history of NSAIDs/Steroids/DMARDs use, and disabilities. Validation test was assessed by calculating the sensitivity, specificity, PPV, NPV, LR+, and ROC curve. Bivariate analysis using Chi Square analysis, and multivariate analysis using logistic regression.Results: The sensitivity test results is best obtained on the question history of NSAIDs/steroids/DMARDs use (100%) and specificity is best obtained on the question about disability (98%). ROC curve analysis which the results >85% obtained on the question of pain >7 days (90%), high degree pain >7 days (93%), and history of NSAIDs/steroids/DMARDs use (92%). LR+ to diagnose rheumatic diseases found in all questions. Chi square analysis showed that all questions were significant with p <0.05 and odds ratio (OR) obtained most on high degree pain more than 7 days (OR: 180.167; 95% CI: 38.196-849.834).Conclusion: The modified COPCORD questionnaire Indonesian version has been adapted and can be a good tool in the screening of joint pain and musculoskeletal diseases compared to examination by rheumatologists. Keyword: Validation, Questionnaire, COPCORD